Representative Group Styles: How Ally Immigrant Rights Organizations Promote Immigrant Involvement. (21st August 2019) - Yukich, Grace; Fulton, Brad R; Wood, Richard L
Abstract: Why are some organizations more successful than others at involving socially diverse groups of people? Previous research emphasizes the role representative leaders play in recruiting diverse constituencies. This study extends that research by analyzing how an organization's group style—its customs that shape everyday interactions—influences constituent involvement by either bridging or reinforcing social divides. Our multi-method approach examines ally immigrant rights organizations to assess the relationship between their group styles and their ability to involve immigrants. Ethnographic data reveal that divergent levels of immigrant involvement in two organizations can be explained by differences in the organizations' group styles—specifically, differences in their religious, class-based, and linguistic practices. Original survey data from a national sample of ally organizations demonstrate the generalizability of our findings. Our analysis shows how having an immigrant-friendly group style can promote immigrant involvement, indicating that an organization's style is associated with its social composition. Having representative leaders from immigrant groups, though positively associated with immigrant involvement, is insufficient for sustaining immigrant involvement; group style can moderate the effect of having representative leaders. This research suggests that organizations seeking to recruit and retain a diverse social base could benefit from cultivating a representative group style.